P165 Surgical lung biopsy in the diagnosis of interstitial lung disease – where are we now?. (15th November 2016) - Brockbank, L; Hilal, E; Johns, L; Walshaw, M; Mohan, K
Abstract : Introduction: With the advent of multidisciplinary team (MDT) working and new therapies in interstitial lung disease (ILD), diagnostic accuracy is increasingly important, and international guidelines 1 have reaffirmed the importance of surgical lung biopsy (SBx) where necessary. However, SBx has associated risks: to assess this further we looked at the diagnostic yield and complication rate of SBx carried out at our regional thoracic centre for patients with ILD. Methods: We looked at all 104 SBxs carried out for ILD over 24 months between 2014–16, collecting data on the nature of the procedure, number of lobes sampled, complications encountered and mortality, and also whether the cases had been discussed at a regional ILD or local radiology MDT meeting prior to SBx. Results: Seventy cases (67%) had been discussed prior to SBx (18 at an ILD MDT). Overall, mean age was 56 years, mean FEV1 79% predicted, FVC 84% predicted, RV 79% predicted, TLC 77% predicted, TLCO 56% predicted, and KCO 77% predicted. All but 3 procedures were carried out by VAT: the median number of lobes sampled was 2 (>1 lobe in 86%), and diagnostic specimens were obtained in 97% (UIP 29%, RB-ILD and DIP 23%, HSP 12%, Sarcoid 10%, NSIP 7%, others 19%). For complications see Table. The mean length of stay was 5.2 days (range 1–44): in-hospital mortality and 30-day mortality were 1% and 3% respectively. Conclusion: Although SBx is here to stay, it has significant morbidity and mortality. Transbronchial cryobiopsy may in the future sit alongside SBx in the diagnostic pathway for ILD, but in addition to offering low morbidity and mortality it must also offer a high diagnostic yield. Reference: Travis WD, Costabel U, Hansell DM, et al . An official American Thoracic Society/European Respiratory Society Statement: Update of the international multidisciplinary classification of the idiopathic interstitial pneumonias. Am J Respir Crit Care Med 2013;188 :733–748.